2020
DOI: 10.3390/jcm9010164
|View full text |Cite
|
Sign up to set email alerts
|

Heart-Type Fatty Acid-Binding Protein (H-FABP) and Its Role as a Biomarker in Heart Failure: What Do We Know So Far?

Abstract: Background: Heart failure (HF) remains one of the leading causes of death to date despite extensive research funding. Various studies are conducted every year in an attempt to improve diagnostic accuracy and therapy monitoring. The small cytoplasmic heart-type fatty acid-binding protein (H-FABP) has been studied in a variety of disease entities. Here, we provide a review of the available literature on H-FABP and its possible applications in HF. Methods: Literature research using PubMed Central was conducted. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 83 publications
0
35
0
3
Order By: Relevance
“…The MG53 supplement prevented the changes (all P < 0.05 vs. CLP group), which were reversed by GW6471 ( P < 0.05 in cTnI and P < 0.01 in CK-MB and LDH vs. CLP+rhMG53 group). H-FABP is a striated muscle abundant cytoplasmic protein that is rapidly released from cytoplasm at the very early stages of myocardial injury [ 30 ]. As shown in Figure 4(e) , myocardial H-FABP was downregulated after CLP ( P < 0.01 vs. sham group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MG53 supplement prevented the changes (all P < 0.05 vs. CLP group), which were reversed by GW6471 ( P < 0.05 in cTnI and P < 0.01 in CK-MB and LDH vs. CLP+rhMG53 group). H-FABP is a striated muscle abundant cytoplasmic protein that is rapidly released from cytoplasm at the very early stages of myocardial injury [ 30 ]. As shown in Figure 4(e) , myocardial H-FABP was downregulated after CLP ( P < 0.01 vs. sham group).…”
Section: Resultsmentioning
confidence: 99%
“…FABPs are a class of small cytoplasmic proteins that facilitate the transfer of fatty acids (FAs) between extra- and intracellular membranes. H-FABP is abundant in myocardial cells [ 37 ] and is released from cytoplasm at almost the onset of myocardial injury [ 30 ]. Chen and Li [ 38 ] reported that circulating H-FABP levels may serve as biomarkers of organ dysfunction in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of fatty-acid binding protein (FABP) were significantly lower in patients compared to controls in this study. This protein family has recently been suggested as a novel marker for the diagnosis of diseases associated with oxidative stress, such as heart diseases, renal failure, Sjögren's syndrome and Alzheimer's disease [49][50][51][52][53]. FABP are intracellular lipid-binding proteins, which exhibit a variety of isoforms depending on the specific organ or cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, at least nine different isoforms have been identified. FABP1 has been suggested as a marker of renal failure, FABP3 as a marker of myocardial infarction, and FABP5 has lately been debated as a diagnostic marker for Sjögren's syndrome [49][50][51][52]. FABP5 was also shown to be highly expressed in nociceptive dorsal root ganglia neurons, and FABP inhibitors exert analgesic properties on a peripheral and supraspinal level.…”
Section: Discussionmentioning
confidence: 99%
“…Since FABPs lack a secretory signal sequence, circulating levels of FABPs have been associated to tissue injury (Hotamisligil and Bernlohr 2015 ). For example, an increase of circulating FABP1 has been correlated with liver damage (Karvellas et al 2017 ), and a serum-FABP3 increase has been considered a marker of heart failure with myocardial injury (Rezar et al 2020 ). FABP4 is released by adipocytes under fasting conditions, and serum FABP4 acts as an adipokine mediating biological effects in different cell types (Cao et al 2006 ).…”
Section: Fabps In Health and Diseasementioning
confidence: 99%